Review: Analisis Komponen Senyawa Kimia Krokot (Portulaca oleraceae L. dan Portulaca grandiflora Hook.): Review: Component Analysis of Purslanes Chemicals Compound (Portulaca oleraceae L. andPortulaca grandiflora Hook.) - Sri Gustini Husein; Melvia Sundalian; Nurul Husna (Jurnal Sains dan Kesehatan, 2021)
Purslanes are medicinal plants from the Portulacaceae family which has more than 100 species, including Portulaca oleraceae L. and Portulaca grandiflora Hook. Both types of purslanes have the potential to become natural medicines due to the presence of active chemical compounds that produce various pharmacological effects. This review compiled the data concerning chemical compounds found in those two types of purslanes, the method of analysis, as well as the factors that affect the quality and quantity of chemical compounds so that they can be used as references in determining natural medicinal ingredients by selecting purslanes based on their desired phytochemical compounds and the appropriate analysis. The data were collected by a method of searching research journals on Google Scholar using certain keywords. From this review, the results showed that the chemical compounds found in the two types of purslanes are phenolic, flavonoid, fatty acid, sterol, terpenoid, and alkaloid. These components can be analyzed using spectroscopic and chromatographic methods for both qualitative and quantitative analysis. Some factors that need to be considered in the analysis of these components are the analytical method used, the method of extraction, the solvents, the plant varieties and genotypes, the part of the plant used, the growth time and harvest time of the sample, and the conditions in which the samples grew.